The ATLAS tau trigger - Casado, M; Belanger-Champagne, C; Benslama, K; Bosman, M; Brenner, R; Czyczula, Z; Dam, M; Demers, S; Farrington, S; Igonkina, O; Kalinowski, A; Kanaya, N; et al. (Elsevier, 2009)
The implementation of a trigger for hadronically decaying tau leptons at the Large Hadronic Collider (LHC) is challenging due to the high background rate, on the other hand it increases tremendously the discovery potential of ATLAS in searches for Standard Model (SM) or Supersymmetric (SUSY) Higgs or other more exotic final states. In this paper we describe the ATLAS tau trigger system, focusing on the early data taking period, and present results from studies based on GEANT 4 simulated events, including trigger rates and the acceptance of tau leptons from SM processes. In order to cope with the rate and optimize the efficiency of important physics channels, the results of the current simulation studies indicate that ATLAS tau triggers should include either relatively high transverse momentum single tau signatures, or low transverse momentum tau signatures in combination with other signatures, such as missing transverse energy, leptons, or jets. © 2009 Elsevier B.V.